Comparison of Spirometric Parameters in different Postures among Young Healthy Volunteers - Mahotra, Narayan B; Shrestha, Lava; Kandel, Sabita; Chaudhary, Sonam (Journal of Nepal Health Research Council, 2023)
Background: Spirometry is the most common pulmonary function tests that specifically measures volume and flow of air during respiration. It helps to identify obstructive and restrictive diseases of the lungs. The alterations of the results in spirometry can happen even in normal health due to change in body postures that alter lung volumes and muscle biomechanics. So, the objective of this study is to determine the effects of change of postures mainly supine, sitting and standing on pulmonary parameters of young healthy volunteers. Methods: A cross-sectional analytical study was conducted among young medical students of Maharajgunj Medical Campus in the department of Clinical Physiology. A total of 31 students were selected by convenient sampling technique. Pulmonary parameters: Forced Vital Capacity (FVC), Forced Expiratory Volume in 1st second (FEV1), FEV1/FVC, Peak Expiratory Flow(PEF), EF2575 were collected from spirometry. The spirometry was done in supine, sitting and standing postures and the best value of each posture was selected for the comparison and obtained data were analyzed using repeated measures ANOVA with confidence interval of 95%. Results: The pulmonary parameters recorded in different postures showed that the mean of these variables comparatively increased in standing posture than others with mean FVC 3.98±0.66 L, mean FEV1 3.53±0.55L, mean FEV1/FVC 89.23±5.60%, mean PEF 8.60±1.62L/s and mean PEF2575 4.46±1.08 L/s. The mean comparisons of these pulmonary parameters in supine, sitting and standing postures showed statistically significant differences with P value < 0.05. Conclusions: The pulmonary parameters are affected by body postures. Those parameters are recorded highest during standing posture and lowest during supine posture. Keywords: Postures; pulmonary parameters; spirometry